Connate water distribution zone affecting groundwater quality of semarang city coastal plain - Mohamed Nor Azhari Azman (Tanjung Malim, 2023)
Connate water distribution zone affecting groundwater quality of semarang city coastal plain by Mohamed Nor Azhari Azman